157k views
5 votes
Perform the indicated operation and write the result in the form . 2(i-14)-i(i+1)

2 Answers

5 votes

Answer:

i-27

Explanation:

We have given an expression .

2(i-14)-i(i+1)

We have to simplify it.

Distribute 2 over first parentheses and -i over second parentheses

2(i)+2(-14)+(-i)(i)+(-i)(1)

2i-28-i²-i

Since, we know that

i² = -1

2i-28-(-1)-i

2i-28+1-i

Add like terms

(2-1)i+(-28+1)

(1)i+(-27)

i-27 which is the answer.

User Anschauung
by
4.3k points
4 votes

Answer:

The simplified form of given expression is -27+i.

Explanation:

The given expression is


2(i-14)-i(i+1)

Use distribution property, to simplify the given expression,


2(i-14)-i(i+1)=2(i)-2(14)-i(i)-i(1)


2(i-14)-i(i+1)=2i-28-i^2-i


2(i-14)-i(i+1)=2i-28-(-1)-i
[\because i^2=-1]

Combine like terms,


2(i-14)-i(i+1)=(-28+1)+(2i-i)


2(i-14)-i(i+1)=-27+i

Therefore the simplified form of given expression is -27+i.

User Hktang
by
4.8k points